Concerning Durkheim's 1899 Lecture 'On Penal Sanctions': Introduction, Translation Notes, and Comments. Issue 1 (1st December 2020) - Datta, Ronjon Paul; Pizarro Noël, François
Abstract: This article provides a critical introduction to the first English translation of Durkheim's Saturday, 2 December 1899, lecture that he entitled 'Course Outline: On Penal Sanctions'. It was written for the first class of the final year of his course 'General Physics of Law and Morality'. We provide some context to the lecture, a description of the four-year long course at Bordeaux of which it was a part, offer notes on our translation, and discuss the salience of its content. Of particular note is Durkheim's sociological reasoning, and the critical impact of antisubjectivism on the development of his special theory of sanctions and conception of morality as part of social reality.